Steep delay discounting and addictive behavior: a meta‐analysis of continuous associations. (1st September 2016) - Amlung, Michael; Vedelago, Lana; Acker, John; Balodis, Iris; MacKillop, James
Abstract: Aims: To synthesize continuous associations between delayed reward discounting (DRD) and both addiction severity and quantity–frequency (QF); to examine moderators of these relationships; and to investigate publication bias. Methods: Meta‐analysis of published studies examining continuous associations between DRD and addictive behaviors. Published, peer‐reviewed studies on addictive behaviors (alcohol, tobacco, cannabis, stimulants, opiates and gambling) were identified via PubMed, MEDLINE and PsycInfo. Studies were restricted to DRD measures of monetary gains. Random‐effects meta‐analysis was conducted using Pearson's r as the effect size. Publication bias was evaluated using fail‐safe N, Begg–Mazumdar and Egger's tests, meta‐regression of publication year and effect size and imputation of missing studies. Results: The primary meta‐analysis revealed a small magnitude effect size that was highly significant ( r = 0.14, P < 10 −14 ). Significantly larger effect sizes were observed for studies examining severity compared with QF ( P = 0.01), but not between the type of addictive behavior ( P = 0.30) or DRD assessment ( P = 0.90). Indices of publication bias suggested a modest impact of unpublished findings. Conclusions: Delayed reward discounting is associated robustly with continuous measures of addiction severity and quantity–frequency. This relation is generally robust across type of addictive behavior and delayed reward discounting assessment modality.